2020
DOI: 10.24251/hicss.2020.532
|View full text |Cite
|
Sign up to set email alerts
|

Determining Digital Transformation Success Factors

Abstract: To understand what organizations do which brings about successful digital transformation (DX), a review of representative literature was performed. From a total of 89 articles, 16 single-case articles which sufficiently documented end-to-end DX success stories of 10 exemplar organizations were selected. Within case content analysis and asking the questions analytical procedure were employed to code each exemplar case, where a total of 174 attributes were found. Making the comparisons procedure was employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…On the one hand, there are studies that consider technology as the main driver of this "radical change" (Morakanyane et al 2020); on the other hand, there are people who describe digital technologies as an enabling factor for a new organizational shift (Nambisan et al 2019; Morakanyane et al 2020) that impacts society and people, as well as, knowledge management (Urbinati et al 2020). Hausberg et al (2018) during their in-depth research on DT identified that big data is the research stream with most contributions while AI and machine learning are those technologies that have a substantial presence.…”
Section: Digital Transformationmentioning
confidence: 99%
“…On the one hand, there are studies that consider technology as the main driver of this "radical change" (Morakanyane et al 2020); on the other hand, there are people who describe digital technologies as an enabling factor for a new organizational shift (Nambisan et al 2019; Morakanyane et al 2020) that impacts society and people, as well as, knowledge management (Urbinati et al 2020). Hausberg et al (2018) during their in-depth research on DT identified that big data is the research stream with most contributions while AI and machine learning are those technologies that have a substantial presence.…”
Section: Digital Transformationmentioning
confidence: 99%
“…When a public sector incorporates digital transformation, it is crucially important to formally communicate the actual narrative for bringing up the change. According to Morakanyane et al [2], the doer must help understand the workers comprehensively why this digitalising is being transformed. This helps in building a concept for the employees and also creates a passion for working for them.…”
Section: Digital Government Transformation Success Factorsmentioning
confidence: 99%
“…It is very important to understand the reason prior to discussing the significance of digital transformation. The rationale to shift towards digital transformation is linked with changing needs of consumers and market dynamics, existing threats with the traditional and conventional methods, and need of innovation to sustain the competitiveness [2]. One reason could be to leverage emerging technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Morakanyane, O'Reilly, and Mcavoy identify the factors predetermining the success of the digital transformation. These factors have been divided into seven groups, among which, in the context of our research, it was necessary to turn into three: cultivate digital culture, develop digital vision, determine digital drivers (Morakanyane et al, 2020). According to Vial, digitalization is a transformational process, resulting in a challenge for organizations as they must change their strategic approach (Vial, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%